Gastric cancer in young patients--is there any hope for them? - Simsa, J; Leffler, J; Hoch, J; Linke, Z; Pádr, R (Acta chirurgica Belgica, 2004)
Gastric cancer usually affects people older than sixty years. This type of cancer is very rare in adults under thirty years of age. In addition, the prognosis in this part of population is grave due to the high incidence of undifferentiated tumours and advanced stage at time of diagnosis. Radical surgery affords the only chance for long term survival, but even this option is often limited upon finding locally advanced disease or peritoneal seeding. The following are case studies of three young adults from a group of 45 patients, who were treated between January 1st, 2000 and December 31st, 2003.
Keywords: analýza přežití; Stomach Neoplasms; Disease Progression; Gastrectomy; Survival Analysis; progrese nemoci; Prognosis; lymfatické metastázy; mužské pohlaví; gastrektomie; adenokarcinom; Adult; kombinovaná terapie; Fatal Outcome; věkové faktory; Lymphatic Metastasis; Neoplasm Staging; ženské pohlaví; prognóza; Humans; Age Factors; staging nádorů; Combined Modality Therapy; dospělí; Female; Adenocarcinoma; fatální výsledek; lidé; Male; nádory žaludku